Is immunisation education in midwifery degrees adequate? - Katie Attwell; Asha Yusuf; Jane Frawley (Taylor & Francis Group, 2019)
Maternal and childhood vaccination decisions begin during pregnancy, and midwives are an important information resource. Their role is set to increase with the expansion of maternal immunisations into new jurisdictions, and new maternal vaccines in development. Meanwhile, other health providers are orienting parents towards vaccine acceptance, using strategies at odds with midwifery norms around information provision and maternal autonomy. To better understand and address the implications of these developments, we conducted a pilot study to ascertain how midwifery students in Australian universities are taught about immunisation, including dedicated time, assessment, who teaches it, and when. We also analysed teaching materials, looking for messaging regarding the importance of vaccination and whether midwives should be advocating for it. We found that education on immunisation comprises less than four hours of the degree, and encountered the norm of midwives informing about rather than recommending vaccination. The considerations we brought to our small project, and what it illuminated, suggest that midwifery university education is an important arena for developing future vaccine advocates. However, midwifery ideology and professional practice mean that such efforts will be challenging, and must commence from a position of respect for the values midwives hold.